THE TEMPERATURE DEPENDENCE OF BYTOWNITE FELDSPAR DISSOLUTION IN NEUTRAL AQUEOUS SOLUTIONS OF INORGANIC AND ORGANIC LIGANDS AT LOW TEMPERATURE (5-35°C) - Welch S.A.; Ullman W.J. (My University, 2000)
The temperature dependence of silica release from bytownite, a Ca-Al-rich feldspar, was determined in solutions of inorganic and organic ligands at neutral pH from 5°C to 35°C. The apparent activation energy of dissolution in the inorganic (distilled water and KNO3) solutions was approximately 10 kcal/mol. The rates and temperature dependence of dissolution in acetate solutions were indistinguishable from those in the inorganic solutions. In contrast, both oxalate and gluconate enhanced the dissolution of the feldspar framework relative to the KNO3 and distilled water controls, presumably by catalyzing Al release from the mineral surface. The apparent activation energy of Si release from feldspar in the oxalate and gluconate solutions was approximately 7 kcal/mol and is due primarily to the larger enhancement of dissolution rates at low temperature. While the catalytic impact of complexing organic ligands on mineral dissolution is clear, this mechanism alone cannot be responsible for the observed biotic enhancement of weathering in field situations.
Keywords: TEMPERATURE DEPENDENCE; BYTOWNITE FELDSPAR DISSOLUTION; LIGANDS